SOCIAL AND EDUCATIONAL FOUNDATIONS FOR DEVELOPING ACCOUNTABILITY SKILLS IN FUTURE PEDAGOGUES (Scientific journal of the Fergana State University, 2025)
This article discusses the theoretical and methodological foundations for developing accountability skills in the professional activities of future pedagogues. It examines the system for preparing future educators to develop accountability skills based on independent learning and evaluates the effectiveness of this preparation. Additionally, the social and educational foundations for developing accountability skills in future pedagogues are analyzed.